Integrating Task-Based Language Teaching in ESP to Enhance Professional Speaking Competence - Yuriatson; Nurul Amaliah; Anwar Taufiq; Nurliah; Asdar (CV. Eureka Murakabi Abadi, 2026)
This study investigates the integration of Task-Based Language Teaching (TBLT) in English for Specific Purposes (ESP) to enhance students' professional speaking competence. Employing a qualitative descriptive design, the study involved seven third-semester nursing students who participated in semi-structured interviews to explore their learning experiences, perceived improvements, and challenges. The data were analyzed using thematic analysis to identify key patterns and insights related to the implementation of TBLT in ESP contexts. The findings reveal that TBLT significantly contributes to the improvement of students' speaking competence, particularly in terms of fluency, vocabulary development, interactional ability, and self-confidence. The use of authentic tasks, such as role plays, simulations, and group discussions, enables students to practice language in meaningful and context-relevant situations, thereby enhancing their ability to communicate effectively in professional settings. Additionally, the interactive and student-centered nature of TBLT fosters greater engagement and motivation among learners. However, the study also identified several challenges, including limited vocabulary, difficulties in spontaneous sentence construction, and initial anxiety in speaking. These challenges indicate the need for adequate instructional support, such as scaffolding strategies, vocabulary enrichment, and constructive feedback. Despite these limitations, students generally expressed positive perceptions of TBLT, highlighting its relevance to their future professional needs. In conclusion, the integration of TBLT in ESP is an effective pedagogical approach for developing professional speaking competence. It not only improves linguistic performance but also enhances learners' confidence and readiness for real-world communication. Therefore, TBLT is recommended as a strategic approach in ESP instruction to better prepare students for the demands of professional communication in global contexts.